Advanced problem solving using Maple : applied mathematics, operation research, business analytics, and decision analysis - Fox, William P., 1949-; Bauldry, William C. (Boca Raton: CRC Press, 2021)
"The advanced text covers dynamical systems, single variable and multi-variable optimization, linear algebra, advanced model fitting techniques, game theory, and multi-attribute decision processes"--
Introduction to problem solving and Maple -- Discrete dynamical models -- Problem solving with single variable optimization -- Problem solving with multi-variable constrained and unconstrained optimization -- Problem solving with linear systems of equations using linear algebra techniques -- Review of regression models and advanced regression models -- Problem solving with game theory -- Introduction to problem solving with multi-attribute decision making.
Includes bibliographical references and index.
Keywords: Maple (Computer file); Mathematical models; Problem solving -- Data processing